Impact of Nickel Intoxication on Ovarian Histology in Oreochromis mossambicus - Sioson, Lovell Cristina; Herrera, Annabelle (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
The effect of chronic sublethal concentration of nickel on ovarian histology in two-month old Oreochromis mossambicus was analyzed histologically. The control ovaries showed abundance of vitellogenic oocytes with smooth and intact membranes and few atretic and previtellogenic oocytes. The ovaries of the fish exposed to 0.5 mg/L nickel sulfate showed wrinkled and deformed oocytes, disrupted theca layers, abundant atretic oocytes in various stages of degeneration and several previtellogenic oocytes. Degenerative changes were worse in the ovaries exposed to 1.0 mg/L nickel sulfate. Proliferation of connective tissues and tissue scars indicated advanced necrosis.